Perilous wagers: gambling, dignity, and day laborers in twenty-first-century Tokyo - Hammering, Klaus K. Y. (Studies of the Weatherhead East Asian Institute, Columbia University, 2024)
"This book depicts the lives of active construction workers in Tokyo's vanishing day-laborer district, San'ya. It asks how one group of men secured sociality and dignity under abject conditions of life, and it shows how they created accountability, dignity, and sociality through the recognition of their peers."--